The role of cloud technologies in the organization of continuous accounting - O.V. Bereznyi (Економіка, управління та адміністрування)
The article examines the role of cloud technologies in the organization of accounting, taking into account changes in traditional management through the introduction of continuous accounting models. Cloud accounting facilitates the seamless integration of real-time data from various sources, such as banks, ERP systems, and point-of-sale terminals, ensuring that information is always up-to-date and accessible. By automating routine tasks such as reconciliation, variance analysis, and transaction matching, cloud accounting reduces the time delays and errors associated with traditional period-end processing, allowing accountants to focus on more strategic value-added activities. Based on cloud technologies, the Continuous Accounting model replaces the traditional approach of fixing information on a specific date with a dynamic workflow that supports continuous financial analysis and decision-making in real-time. This approach increases operational efficiency, accuracy, and responsiveness, providing management with timely information on economic indicators. In addition, the article examines the challenges of implementing cloud accounting, including data security, system stability, and authentication, emphasizing the need for robust security measures and comprehensive risk management strategies. By leveraging cloud accounting, businesses can significantly improve financial transparency, productivity, and cost-effectiveness, ultimately contributing to better strategic planning and business success. The results of the study emphasize the transformational potential of cloud technologies in shaping the future of financial management and accounting practices.